Is nucleo-cytoplasmic incompatibility the reason of acceleration polar body extrusion? (International Journal of Current Engineering and Technology, 2014)
Timing extrusion of the first polar bodies (PBs) is significantly accelerated of fully grown germinal vesicle (GV) cytoplasts reconstituted with embryonic/somatic nuclei during maturation through unknown mechanism. The aim of the present study was to determine timing extrusions of PBs throughout combinations of recipient cytoplasts with donor nuclei and enucleolation of GV oocytes. The recipient cytoplasts usd were cytoplasts of fully grown germinal and metaphase I (MI) oocytes. The donor nuclei used were karyoplasts of growing and fully grown germinal vesicle oocytes; nucleolated and anuclolated G2 nuclei of 1/2-blastomeres; G2 and M-phase nuclei of 1/4-blastomeres. In addition, fully grown germinal vesicle oocytes were enucleolated. Timing of germinal vesicle breakdown and polar body extrusion and nuclear morphology were monitored upon introducing the donor nuclei into recipient cytoplasts. The results indicated that germinal vesicle breakdown (GVBD) and polar body extrusion were extended/delayed of GV cytoplasts reconstructed with GVgr karyoplasts (karyoplasts of growing oocytes) compared with those reconstructed with GV karyoplasts (karyoplasts of fully grown oocytes) as well as control and enucleolated oocytes. Timing extrusions of PBs were not differed between GV cytoplasts reconstituted either with nucleolated or anucleolated donor nuclei.Timing extrusions of PBs and percentage of maturation (17h of maturation) were differed between G2 and M-phase donor nuclei (1/4-blastomere) which introduced into MI (metaphase I) cytoplasts. It might be concluded that nucleo-cytoplasmic incompatibility might be the reason of acceleration of PB extrusions.
Keywords: Nucleo-cytoplasmic; enucleolation; polar body; acceleration; extrusion